Penyuluhan Terapi Nonfarmakologi untuk Nyeri Sendi pada Penderita Gout Arthritis - Adhin Al Kasanah; Mega Arianti Putri; Binar Wahyuning Widhi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Gout arthritis is an inflammatory joint condition that causes severe pain and impacts the patient's quality of life. Joint pain management involves more than just pharmacological therapy using medications; it also requires non-pharmacological approaches. The goal of this community service activity is to improve the knowledge and skills of gout arthritis sufferers in managing joint pain using various non-pharmacological therapy modalities. The results of the community service program indicate an increase in knowledge about non-pharmacological management of joint pain in gout arthritis patients. Non-pharmacological therapy education is an effective way to help people with gouty arthritis manage their joint pain. The significant increase in knowledge following the intervention demonstrates the importance of ongoing education and hands-on demonstrations. The next step is to increase the scope of education and support for the implementation of non-pharmacological therapies in various communities to ensure sustainability.